Magic light with a musical bell / Aini Mohamed Shariff and Norshakila Haris - Mohamed Shariff, Aini; Haris, Norshakila (2003)
This simple project ‘Magic Lights with a Musical Bell’ is valuable, acceptable and interesting for use in the house, despite it can also be use as a security system. The main purpose of the project is to facilitate the resident of the house where it save energy, money and electricity. Beside that, it can give advantages to the blind person by knowing the presence of the person from the sound produced. With a total expanse of RM 60.60, it is suitable for the residence of the house who are budgeting their money. T he circuit operate by sensing the presence of a person that switch on the lights at the entrance gate to a premises, at night, automatically. In addition, it sounds a musical bell to signify the presence of the person. The lamp is switched on only for a short interval to save electricity.